Two Years in the Forbidden City - Der Ling, Princess, 1886-1944 (Salt Lake City, UT : Project Gutenberg, 1997)
"Two Years in the Forbidden City" by Princess Der Ling is a historical account written in the early 20th century. The narrative recounts the unique experiences and observations of the author as the First Lady-in-Waiting to the Empress Dowager Cixi of China. It offers intimate insights into the life within the Imperial Palace, focusing on the court's intricate customs, the personalities of its members, and the societal changes occurring during a pivotal time in Chinese history. The beginning of the book introduces Princess Der Ling's family background and their arrival in Shanghai. As part of a high-ranking family with a progressive father, she describes the complexities of their transition from living in Paris to returning to China. The narrative highlights her father's struggle for reform against a conservative backdrop and sets the stage for Princess Der Ling's appointment at the court. Her vivid recollections as she first travels to the Summer Palace to meet the Empress Dowager Cixi reveal her excitement and trepidation, providing readers with a glimpse of the lavish and constricted world of the Qing Dynasty's last empress. (This is an automatically generated summary.)
Release date is 1997-04-01
Produced by Charles Keller for Sarah, and by David Widger
Keywords: Cixi, Empress dowager of China, 1835-1908 -- Anecdotes; Empresses -- China -- Anecdotes; China -- Court and courtiers -- Anecdotes